EMPIRICAL ANALYSIS OF FACTORS INFLUENCING THE GRANTING OF PRELIMINARY INJUNCTIONS IN PERNAMBUCO'S FEDERAL COURT - Silva, Renan Francelino; Silva, Rafael Cândido; Oliveira, Camila; Gomes Neto, José Mário (Revista de Ciências Jurídicas e Sociais da UNIPAR, 2024)
What does influence the issuance of Preliminary Injunctions (in limine) in Writs of Mandamus within the jurisdiction of Pernambuco's Federal Court? To protect citizens against abuse of power or illegality committed by a member of the Public Administration, the Federal Constitution provides the writ of mandamus as a procedural instrument (section 5, subsection LXIX and LXX, of the Brazilian Federal Constitution, and the Law No. 12.016/09). Existing literature in the fields of procedure law and administrative law highlights the potential conflicts and violations of clear and indisputable rights that can arise from the improper granting or denial of preliminary injunctions. This article aims to empirically examine, through logistic regression analysis (logit), the factors that influence the issuance of Preliminary Injunctions (in limine) in Writs of Mandamus within the jurisdiction of Pernambuco's Federal Court.